The Role of OCB in Mediating The Effect of Employee Engagement and Organizational Commitment on Employee Performance: Contract vs Permanent Employees - Fatoni, Mahmud; Prihatini, Dewi; Barokah Suryaningsih, Ika (International Journal of Scientific Research and Management (IJSRM), 2018)
Banking industry is one of sector that relies its employees on its quality of human capital. In facing the organizational change in the form of digitaliation, the performances of employees are really challenged.  This study seeks to test the role of Organizational Citizenship Behavior (OCB) as mediator of the effect of employee engagement and organizational commitment  on the employees performance at PT. BCA, Tbk Jember branch, Indonesia.  This study used quantitative approach. As many as 162 employees are involved as respondents. We differ them based on their employee types, those are contract and permanent employees. The analytical tool used is path analysis. We report that there is a significant indirect effect of employee engagement and organizational commitment on employees performance through OCB. The role of OCB as mediator is significant in both of effects. We also found that employee engagement and organizational commitment have a significant direct effect on employee performance, employee engagement and organizational commitment have a significant direct effect on OCB, and OCB has a significant direct impact on employee performance.